Patrolling the boundaries of social domains: Neural activations to violations of expectations for romantic and work relationships. (3rd September 2021) - Bland, A. R.; Zahn, R.; Elliott, R.; Taylor, J. R.; Hill, J.
ABSTRACT: According to the social domains hypothesis, we reduce the information-processing demands of complex social cues by classifying them into a limited number of domains, each with distinct sets of expectations. This requires rapid identification of violations of the boundaries between social domains. We hypothesized that these violations are likely to be associated with neural activation of the salience system. Using fMRI we compared responses of 20 adults to expected and unexpected everyday social scenarios in personal and work interactions. The vignettes exemplified different kinds of scenarios presented in the work setting, i.e., task-focused scenarios which are expected at work and scenarios with a personal focus, which are unexpected at work. The key contrast between task and personal focussed scenarios presented in the work setting was associated with fronto-insular activation. Perceived inappropriateness of the unexpected scenarios, and shorter response time to judgment of inappropriateness were also associated with fronto-insular activation, after controlling for unpleasantness. This study indicates specific neural responses to violations of expectations in different social situations. Our findings suggest that the fronto-insular region is implicated in rapid detection of behaviors that cross the boundaries of social domains, which are hypothesized to be necessary for efficient social information processing.